"Giving us hope": Parent and neonatal staff views and expectations of a planned family‐centred discharge process (Train‐to‐Home). (21st December 2016) - Ingram, Jenny; Redshaw, Maggie; Manns, Sarah; Beasant, Lucy; Johnson, Debbie; Fleming, Peter; Pontin, David
Abstract: Background: Preparing families and preterm infants for discharge is relatively unstructured in many UK neonatal units (NNUs). Family‐centred neonatal care and discharge planning are recommended but variable. Design and participants: Qualitative interviews with 37 parents of infants in NNUs, and 18 nursing staff and 5 neonatal consultants explored their views of discharge planning and perceptions of a planned family‐centred discharge process (Train‐to‐Home). Train‐to‐Home facilitates communication between staff and parents throughout the neonatal stay, using a laminated train and parent booklets. Results: Parents were overwhelmingly positive about Train‐to‐Home. They described being given hope, feeling in control and having something visual to show their baby's progress. They reported positive involvement of fathers and families, how predicted discharge dates helped them prepare for home and ways staff engaged with Train‐to‐Home when communicating with them. Nursing staff reactions were mixed—some were uncertain about when to use it, but found the visual images powerful. Medical staff in all NNUs were positive about the intervention recognizing that it helped in communicating better with parents. Conclusions: Using a parent‐centred approach to communication and informing parents about the needs and progress of their preterm infant in hospital is welcomed by parents and many staff. This approach meets the recommended prioritization of family‐centred care for such families. Predicted discharge dates helped parents prepare for home, and the ways staff engaged with Train‐to‐Home when communicating with them helped them feel more confident as well as having something visual to show their baby's progress.